ChemInform Abstract: Palladium‐Catalyzed Addition Reaction of Thioesters to Norbornenes. Issue 1 (17th December 2015) - Arisawa, Mieko; Tanii, Saori; Yamada, Tomoki; Yamaguchi, Masahiko
Abstract: A palladium complex derived from Pd2 (dba)3 and tris(2, 4, 6‐trimethoxyphenyl)phosphine catalyzes the addition reaction of thioesters to norbornenes, giving the trans‐2‐acyl ‐3‐organothionorbornanes predominantly with the acyl group at the endo‐position and the organothio group at the exo‐position.